Contribution Body Height, Arm Muscle Strength, and Flexibility Smash Ability Badminton among University Students - Hasanuddin, M. Imran; Satrianingsih, Baiq; Primayanti, Intan (Sportify Journal, 2022)
Badminton smash performance requires the integration of anthropometric characteristics, upper-limb strength, flexibility, and sport-specific stroke execution. This study examined the contribution of body height, arm muscle strength, and flexibility to badminton smash performance among students of the Faculty of Sport Science, Universitas Negeri Makassar. A quantitative descriptive-correlational design with regression analysis was used. The sample consisted of 40 students who had programmed badminton coursework. Body height was measured using an anthropometric height test, arm muscle strength through a 20-second push-up test, flexibility through a backward trunk-flexibility test, and smash performance through a badminton smash skill test. Data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, simple regression, and multiple regression. The findings showed that body height, arm muscle strength, and flexibility were positively and significantly correlated with smash performance. In the multiple regression model, the three predictors jointly explained 69.8% of the variance in smash performance, with arm muscle strength emerging as the strongest predictor. However, flexibility was not a significant partial predictor after body height and arm muscle strength were controlled. These findings indicate that smash performance is primarily supported by upper-limb strength, while body height and flexibility function as complementary physical factors. Training programs should integrate arm-strength development, flexibility exercises, anthropometric consideration, and smash-specific technical practice.